On ill-posedness of the numerical inversion inverse problem of one-dimensional convolution - Sultanov, M.A.; Koshanova, M.D.; Ustemirova, B.B. (Bulletin of the Karaganda University. Mathematics Series, 2016)
In the article the method of numerical simulation shows the ill-posedness of the inverse problem of the numerical treatment of one-dimensional convolution.Built discrete convolution model.Calculation performed in the absence and presence of noise. Computer computing experiments have shown that the neglect of an error that occurs when measuring in practical cases, can lead to incorrect results. One easy way to restore the correct numerical convolution, Numerical examples are also given.